Opportunities and Challenges of a Filipino Educator in a Home-based Online EFL Industry: A Single Case Study - Marlon Pontillas (Camarines Sur Polytechnic Colleges, 2021)
Filipino educators are known for their remarkable traits in the teaching profession here and abroad. One of the most in-demand fields is English teachers. Studies have shown that non-native speakers have high regard for Filipino teachers in ESL/EFL schools. Because of the availability of technology in today's time, Filipino teachers do not need to go abroad to teach international students. This study utilized a single-case research method with a single participant who has been in the online industry for almost eight years now. Teacher John of Company A shared his experience highlighting the opportunities and challenges he encountered as a home-based online teacher. The study is guided with constructivism as the main framework of the study and thematic analysis to generate the themes of the data. The themes identified include: background of the participant; the application process; adjustment and investment to the company; handling a class; company rules and regulations; personal and professional development. The findings of the study showed that the opportunities and challenges faced by online teachers paved the way for their personal and professional development. The researcher recommended that other researchers could explore factors affecting the computer-mediated set-up of English language teaching.